Medical- and Non-Medical-Grade Polycaprolactone Mesh Printing for Prolapse Repair: Establishment of Melt Electrowriting Prototype Parameters - Maria F. R. Vaz; Joana A. P. Martins; Fábio Pinheiro; Nuno M. Ferreira; Sofia Brandão; Jorge L. Alves; António A. Fernandes; Marco P. L. Parente; Maria E. T. Silva (Applied Sciences)
Pelvic organ prolapse (POP) occurs due to inadequate support of female pelvic organs and is often treated with synthetic implants. However, complications like infections, mesh shrinkage, and tissue erosion can arise due to biomechanical incompatibilities with native tissue. This study aimed to optimize the melt electrowriting process using medical-grade biodegradable Poly(ε-caprolactone) (PCL) with a pellet extruder to print meshes that mimic the mechanical properties of vaginal tissue. Square and diagonal mesh designs with filament diameters of 80 µm, 160 µm, and 240 µm were produced and evaluated through mechanical testing, comparing them to a commercial mesh and sheep vaginal tissue. The results showed that when comparing medical-grade with non-medical-grade square meshes, there was a 54% difference in the Secant modulus, with the non-medical-grade meshes falling short of matching the properties of vaginal tissue. The square-shaped medical-grade PCL mesh closely approximated vaginal tissue, showing only a 13.7% higher Secant modulus and a maximum stress of 0.29 MPa, indicating strong performance. Although the diagonal-shaped mesh exhibited a 14% stress difference, its larger Secant modulus discrepancy of 45% rendered it less suitable. In contrast, the commercial mesh was significantly stiffer, measuring 77.5% higher than vaginal tissue. The diagonal-shaped mesh may better match the stress–strain characteristics of vaginal tissue, but the square-shaped mesh offers stronger support due to its higher stress–strain curve. Overall, meshes printed with medical-grade PCL show superior performance compared to non-medical-grade meshes, suggesting that they are a promising avenue for future advancements in the field of POP repair.